On-farm research with annual crops - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
On-farm research with annual crops: some biometrical considerations by F Lauckner and W Fielding 1995 16pp price $50 ISBN 976 8139 42 0